Optimal Monetary Policy with Overlapping Generations of Policymakers - Shamloo, Maral (Washington, D.C. : International Monetary Fund, 2010)
In this paper I study the effect of imperfect central bank commitment on inflationary outcomes. I present a model in which the monetary authority is a committee that consists of members who serve overlapping, finite terms. Older and younger generations of Monetary Policy Committee (MPC) members decide on policy by engaging in a bargaining process. I show that this setup gives rise to a continuous measure of the degree of monetary authority's commitment. The model suggests that the lower the churning rate or the longer the tenure time, the closer social welfare will be to that under optimal commitment policy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Monetary Policy; MPC Member; Objective Function; Standard Deviation; WP; United Kingdom